Metagenomic analysis demonstrates the diversity of the fecal virome in asymptomatic pigs in East Africa - Amimo, Joshua O.; El Zowalaty, M.E.; Githae, D.; Wamalwa, M.; Djikeng, Appolinaire; Nasrallah, G.K. (Springer, 2016)
Pigs harbor a variety of viruses that are closely related to human viruses and are suspected to have zoonotic potential. Little is known about the presence of viruses in smallholder farms where pigs are in close contact with humans and wildlife. This study provides insight into viral communities and the prevalence and characteristics of enteric viral co-infections in smallholder pigs in East Africa. Sequence-independent amplification and high-throughput sequencing were applied to the metagenomics analysis of viruses in feces collected from asymptomatic pigs. A total of 47,213 de novo-assembled contigs were constructed and compared with sequences from the GenBank database. Blastx search results revealed that 1039 contigs (>200 nt) were related to viral sequences in the GenBank database. Of the 1039 contigs, 612 were not assigned to any viral taxa because they had little similarity to known viral genomic or protein sequences, while 427 contigs had a high level of sequence similarity to known viruses and were assigned to viral taxa. The most frequent contigs related to mammalian viruses resembling members of the viral genera Astrovirus, Rotavirus, Bocavirus, Circovirus, and Kobuvirus. Other less abundant contigs were related to members of the genera Sapelovirus, Pasivirus, Posavirus, Teschovirus and Picobirnavirus. This is the first report on the diversity of the fecal virome of pig populations in East Africa. The findings of the present study help to elucidate the etiology of diarrheal diseases in pigs and identify potential zoonotic and emerging viruses in the region. Further investigations are required to compare the incidence of these viruses in healthy and diseased pigs in order to better elucidate their pathogenic role.